Effects of RP58866 on transmembrane K+ currents in mammalian ventricular myocytes. - Yang Bao-feng; Li Gui-rong; Xu Chang-qing; Nattel Stanley (Acta Pharmacologica Sinica, 2016)
AIM: To determine effects of RP58866 on inward rectifier K+ current (IKl), transient outward K+ current (Ito) and delayed outward rectifier K+ current (IK) in isolated cardiac myocytes. METHODS: In isolated ventricular myocytes of guinea pig and dog, the effect of RP58866 on IKl, Ito, and IK were observed by the whole cell voltage-clamp technique. RESULTS: RP58866 decreased IKl in a concentration-dependent manner, with an IC50 of (3.4 +/- 0.8) micromol.L-1 (n = 6) at -100 mV in guinea pig ventricular cells. In dog ventricular myocytes, RP58866 inhibited Ito with IC50 of (2.3 +/- 0.5) micromol.L-1 at +40 mV. In guinea pig ventricular cells, RP58866 at 100 micromol.L-1 decreased IK: IKstep by (58 +/- 13)% at +40 mV, and IKtail by (86 +/- 17)%, respectively. RP58866 inhibited IKstep with an IC50 of (7.5 +/- 0.8) micromol.L-1, and IKtail with an IC50 of (3.5 +/- 0.9) micromol.L-1. The envelope of tail analysis suggested that both IKr and IKs were inhibited. CONCLUSION: RP58866 inhibits IKl, Ito, and IK in cardiac myocytes with a similar potency, and is not a specific IKl inhibitor.